1976
DOI: 10.1038/bjc.1976.81
|View full text |Cite
|
Sign up to set email alerts
|

Response of remission lymphocytes to autochthonous leukaemic myeloblasts

Abstract: Summary.-Thymidine incorporation in vitro by remission lymphocytes from a total of 6 patients with acute myeloid leukaemia (AML) was measured following stimulation by autochthonous and allogeneic AML blasts and cell lines. The early peak response to autochthonous blasts in 2 of these patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our results seem to agree with those published by Schweitzer et al [13] who concluded that MCC was unsuitable for the detection of immunity against leukaemia-associated antigens; in fact, they described that the in creased thymidine incorporation occasional ly observed in mixed cultures of leukaemia cells and remission lymphocytes could not be distinguished from non-specific thymi dine incorporation as was shown to occur sometimes in unstimulated cultures. Howev er, a recent publication [14] showed a sig nificant autologous stimulation with an ear ly peak response at 48-72 h in 2 of 6 AML patients tested. Positive responses were ob tained with stimulating blasts (S) and re sponding lymphocytes (R) at a ratio of S : R of 1:1.5.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results seem to agree with those published by Schweitzer et al [13] who concluded that MCC was unsuitable for the detection of immunity against leukaemia-associated antigens; in fact, they described that the in creased thymidine incorporation occasional ly observed in mixed cultures of leukaemia cells and remission lymphocytes could not be distinguished from non-specific thymi dine incorporation as was shown to occur sometimes in unstimulated cultures. Howev er, a recent publication [14] showed a sig nificant autologous stimulation with an ear ly peak response at 48-72 h in 2 of 6 AML patients tested. Positive responses were ob tained with stimulating blasts (S) and re sponding lymphocytes (R) at a ratio of S : R of 1:1.5.…”
Section: Discussionmentioning
confidence: 91%
“…Stimulation of remission lymphocytes by autologous blasts has been reported by some authors [3,10,14,16], while others [13] failed to demon strate this phenomenon. Antibodies against either autologous or allogeneic blast cells have been found in the sera of leukaemic patients [2,6].…”
Section: Introductionmentioning
confidence: 97%
“…AML patients in whom bone marrow remission was induced by chemotherapy consisting of cytosine arabinoside (Ara-C) and daunorubicin (DR) (Taylor et al, 1976b) are described. The assessment of remission is described elsewhere (Freeman et al, 1973;Taylor et al, 1976b).…”
Section: Patients and Controlsmentioning
confidence: 99%
“…Acute leukaemias express lymphocyteactivating determinants which stimulate autologous and allogeneic lymphocytes (Taylor et al 1976;Han et al, 1977). Family studies indicate that LAD on leukaemic blasts may be encoded by the MHC, though stimulation of autologous and HLAidentical sib lymphocytes by these cells suggest the expression of other, possibly leukaemia-specific, LAD (Reinsmoen et al, 1978;Zier et al, 1980).…”
mentioning
confidence: 99%